Chromatin Modification and Remodeling in Heart Development - Paul Delgado-Olguín; Jun K. Takeuchi; Benoit G. Bruneau (The Scientific World Journal)
In organogenesis, cell types are specified from determined precursors as morphogenetic patterning takes place. These events are largely controlled by tissue-specific transcription factors. These transcription factors must function within the context of chromatin to activate or repress target genes. Recent evidence suggests that chromatin-remodeling and -modifying factors may have tissue-specific function. Here we review the potential roles for chromatin-remodeling and -modifying proteins in the development of the mammalian heart.